2010
DOI: 10.1097/meg.0b013e32833efdb2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol, tobacco and caffeine consumption and vegetarian diet on gallstone prevalence

Abstract: The factors like tobacco and caffeine consumption as well as vegetarian diet exerted no measurable effect on the prevalence of gallstones. A protective effect was found for alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
5
28
3
Order By: Relevance
“…vasoactive intestinal peptide), as hypothesized in cirrhotic patients. Although caution is required in the interpretation of data and doses of alcohol might vary, the presence of a normal fasting gallbladder volume and faster and more efficient gallbladder emptying might partially explain the potentially protective effect against the development of gallstones which is shown for alcohol consumption in the absence of liver cirrhosis . Interestingly, this putative protective effect on gallstone risk disappeared after one year of abstinence.…”
Section: Discussionsupporting
confidence: 91%
“…vasoactive intestinal peptide), as hypothesized in cirrhotic patients. Although caution is required in the interpretation of data and doses of alcohol might vary, the presence of a normal fasting gallbladder volume and faster and more efficient gallbladder emptying might partially explain the potentially protective effect against the development of gallstones which is shown for alcohol consumption in the absence of liver cirrhosis . Interestingly, this putative protective effect on gallstone risk disappeared after one year of abstinence.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have reported an inverse association between alcohol intake and incidence of gallstones [1,21,43,44,45], however several studies failed to find any association [46,47,48,49]. Völzke et al [1] reported an OR of 0.77 (95% CI 0.54–1.09, p = 0.14) in men consuming 0–20 g alcohol per day.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Indeed, caffeine and possibly other components found in coffee may alter serum lipids and influence enterohepatic bile salt circulation, however further evidence is needed as some studies have failed to find any association [45,49,59], whereas others even report an increased risk of gallstones with coffee consumption [1,46,60] – differences that might reflect ethnic and/or complex gene-environment interactions.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…After adjusting for many confounders, observational studies have demonstrated a significant correlation between light or moderate alcohol use and reduced risk of several diseases and health problems, as shown in the following list: • Alzheimer's disease/dementia [1][2][3] • Asthma [4] • Autoimmune hypothyroidism [5] • Colorectal cancer [6] • Common cold [7] • Coronary heart disease [8,9] • Diabetes (type 2) [10] • Gallstones [11] • Hearing loss [12,13] • Intermittent claudication [14] • Liver cirrhosis [15] • Low birth weight, prematurity [16] • Lower urinary tract symptoms (in men) [17] • Metabolic syndrome [18] • Negative child development [19][20][21] • Osteoporosis [22][23][24][25] • Overweight [26][27][28] • Psychiatric disorders [29][30][31][32] • Renal cell cancer [33] • Rheumatoid arthritis [34][35][36] • Stroke (ischaemic) [37] • General health status [38,39] • All cancer mortality [40] • Total mortality [41] For the majority of these diseases and health problems, the correlation has been confirmed in more than one study. For seven of these, several studies and metaanalyses have been published...…”
Section: Introductionmentioning
confidence: 99%